Self-Adjustment of Overseas Students during the Covid-19 Pandemic in Makassar City - Irdianti, Irdianti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The COVID-19 pandemic has made overseas students faced various changes and differences in various aspects of life that require adjustment. This study analyzes the adjustment process for overseas students in Makassar City using five aspects proposed by Haber and Runyon (2006), including aspects of accurate perception of reality, ability to cope with stress and anxiety, self-image, ability to express feelings, and good interpersonal abilities. This study uses a phenomenological approach. Data mining was carried out by observation and structured interviews. This study concludes that the two overseas students showed self-adjusting behavior by trying to build resilience and develop self-awareness, using active coping to the problems they faced, trying to create meaning and hope, establishing good intrapersonal relationships, trying to control and stabilize emotions. The dominant inhibiting factors are academic and cultural. Social support factors and the desire to develop themselves and get psychological well-being are factors that support overseas students in adjusting themselves.